PERAN BKM (BADAN KEMAKMURAN MASJID) DALAM MEMAKMURKAN MASJID GAMPONG LIMPOK ACEH BESAR - A’la, Rafiqul; Habibi, Khairul; Kamaruddin, Kamaruddin (STKIP Pesisir Selatan, 2025)
Mosques are important places for worship and Islamic activities, but they are often under-active, especially in rural areas. This study examines how the Mosque Welfare Agency (BKM) revitalizes the Nurul Huda Mosque in Gampong Limpok, Aceh Besar, and the challenges it faces. The study employed a descriptive qualitative method. Data were collected through in-depth interviews, direct observation, and related documents. Data were continuously analyzed to identify patterns and conclusions. The results show that the Nurul Huda Mosque, which began operating in 2016 with a large capacity and complete facilities, is revitalized by the competent BKM. The BKM is very active in holding regular religious activities such as religious studies, lectures, Yasinan (the recitation of the Yasin), and Friday sermons. They also organize social activities such as youth activities, competitions, maulid (the Prophet's birthday), meetings, and mutual cooperation (gotong royong). However, the BKM faces challenges such as a lack of funding, low youth participation, and disagreements among administrators. To address these challenges, the BKM raises funds, collaborates with other institutions, and holds internal meetings. The conclusion is that the BKM of the Nurul Huda Mosque is crucial and has successfully revitalized the mosque through various activities. Despite funding and internal challenges, the BKM continues to strive to make mosques the center of community activities.